Upaya Meningkatkan Hasil Belajar Siswa Menggunakan Model Pembelajaran Kooperatif Tipe Teams Games Tournaments (TGT) Berbantuan Media Prezi Dalam Materi Perakitan Komputer - Oktarika, Dini; Putri, Nur Fitriani Massilawati (Universitas Nusantara PGRI Kediri, 2019)
The purpose of this study was to improve student learning outcomes using cooperative learning models Teams Games Tournaments type assisted by Prezi media in computer assembly material in multimedia X grade students of SMK Negeri 1 Sekadau Hilir Sekadau Regency. The method used in this study is the method of action research and the form of research is classroom action research with the use of cycles, where the stages of each cycle are planning, implementation, observation, reflection. Based on the results of the study, it was obtained 1) The teacher learning process in the first cycle of 66.67% was included in the